Money Doesn?t Buy Happiness ... Or Does It? : A Reconsideration Based on the Combined Effects of Wealth, Income and Consumption - Bruce Headey; Ruud Muffels; Mark Wooden (Institute for the Study of Labor (IZA), 2004)
The accepted view among psychologists and economists alike is that economic well-being has a statistically significant but only weak effect on happiness/subjective well-being (SWB). This view is based almost entirely on weak relationships with household income. The paper uses household economic panel data from five countries – Australia, Britain, Germany, Hungary and the Netherlands – to provide a reconsideration of the impact of economic wellbeing on happiness. The main conclusion is that happiness is considerably more affected by economic circumstances than previously believed. In all five countries wealth affects life satisfaction more than income. In the countries for which consumption data are available (Britain and Hungary), non-durable consumption expenditures also prove at least as important to happiness as income. Further, results from panel regression fixed effects models indicate that changes in wealth, income and consumption all produce significant, though not large, changes in satisfaction levels.
Keywords: D19; D31; I31; 330; consumption; economic well-being; income; life satisfaction; subjective wellbeing; wealth; Lebensstandard; Lebensqualität; Einkommen; Vermögen; Konsumgesellschaft; Schätzung; Australien; Grossbritannien; Deutschland; Ungarn; Niederlande; Lebenszufriedenheit